2013
DOI: 10.1007/s11626-013-9706-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effects of human umbilical cord extracts on human fibroblasts, keratinocytes, and melanocytes

Abstract: Skin aging is the result of internal and external factors. So-called photoaging has been identified as the major factor in skin aging. Effects of photoaging include inhibition of fibroblast and keratinocyte proliferation as well as collagen and fibronectin expression, while activating expression of collagenases such as matrix metalloproteinase-1. Previous studies have shown that extracts or products from human placenta significantly improve skin aging and chronic wound healing. However, there are few studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Moreover, it is a visible organ that allows assessment of the health and well-being of an individual and reflects many aesthetic parameters [1][2][3]. Similar to other biological components of human body, the skin is subjected to a complex and cumulative ageing process throughout life, which occurs due to structural and physiological changes caused by factors that are intrinsic and extrinsic to the body [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a visible organ that allows assessment of the health and well-being of an individual and reflects many aesthetic parameters [1][2][3]. Similar to other biological components of human body, the skin is subjected to a complex and cumulative ageing process throughout life, which occurs due to structural and physiological changes caused by factors that are intrinsic and extrinsic to the body [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord can be mixed, filtrated or pelleted, the extract increases the in vitro proliferation and migration of fibroblasts, as described in the literature (Van Pham et al, 2014;Bakhtyar et al, 2017;Nagaishi et al, 2017;Saito et al, 2018). Original data from our laboratory have shown that increasing protein concentrations of HUC extract enhance fibroblast proliferation (after 48 h) and migration (16 h) (Figure 2).…”
Section: Huc Byproduct: Extractsmentioning
confidence: 84%
“…In fact, CB is an integral part of fetal blood [5,6]. Doctors call umbilical cord blood liquid gold, scientists -the greatest success story in the field of cell technology [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…CB also differs from adult blood in rheological and immunological characteristics [6,9], coagulation parameters [7], and oxygen transfer, which allows the use of fetal erythrocytes in severe forms of hemorrhagic shock accompanied by secondary tissue hypoxia [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation